Nursing diagnoses in hospitalized patients with COVID-19 in Indonesia - Nur Hidayati; Farhan Hadi; Suratmi Suratmi; Isni Lailatul Maghfiroh; Esti Andarini; Henri Setiawan; Yudisa Diaz Lutfi Sandi (Belitung Nursing Journal, 2022)
Background: The COVID-19 pandemic has become a global public health issue, and the roles of nurses are very much needed in providing nursing services in the current situation. The enforcement of appropriate nursing diagnoses for patients with COVID-19 is also fundamental in determining proper nursing care to help the patients achieve maximum health. Objective: This study aimed to describe and analyze nursing diagnoses in patients with COVID-19 treated in the isolation rooms and ICUs. Methods: This study used a secondary data analysis from hospital medical record data of patients with COVID-19 from early December 2020 to the end of February 2021. Data were selected using a cluster random sampling technique and analyzed using descriptive statistics. Results: The results showed that the signs and symptoms of the patients with COVID-19 that often appeared were fever, cough, shortness of breath, and decreased consciousness. The common nursing diagnoses in the hospitalized patients with COVID-19 were hyperthermia, ineffective airway clearance, gas exchange disorder, self-care deficit, spontaneous ventilation disorder, spontaneous circulation disorder, knowledge deficit, and shock risk. Conclusion: This study offers an insight into nursing practices in the hospital setting, which can be used as a basis for nurses to perform complete nursing assessments and nursing diagnoses during the pandemic.